PERANG AFGANISTAN ANTARA AMERIKA SERIKAT DAN TALIBAN TAHUN 2021: ANALISIS TRINITAS PERANG CLAUSEWITZ - Muhammad Izzu Saukani (Indonesian Journal of International Relations, 2023)
This article analyzes the Afghanistan war between the United States and the Taliban in 2021 through the Clausewitz war trinity in terms of the success or failure of the war. Analysis used a qualitative-explanative approach and literature study methods in collecting data, and using the Trinity of War theory as an analytical tool. The results of the study show that the trinity of war aspect, which consists of the people, the military and the government, has a major influence on the outcome of the US war in Afghanistan. The US decision to withdraw all its troops and allies in the Afghanistan war is considered a form of failure in this war. Nevertheless, this article does not deny that these conditions do not describe the failure to achieve the US political goals themselves, namely the assassination of the leader of the international terrorist organization (al-Qaida) Osama bin Laden as the main objective of the war